Best mean-square approximation of functions defined on the real axis by entire functions of exponential type - Vakarchuk, S. B. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
Exact constants in Jackson-type inequalities are calculated in the space L_2 (R) in the case where the quantity of the best approximation A_σ(f) is estimated from above by the averaged smoothness characteristic Φ_2(f, t) = 1t ^t_0||Δ^2_h(f)||dh. We also calculate the exact values of the average u-widths of classes of functions defined by Φ_2.